Boosting Adolescent English Proficiency: Psycholinguistic Benefits of Mobile Platforms - Ibrahim, Mona Kamal; Glushkov, Sergey (International Journal of Interactive Mobile Technologies (iJIM), 2024)
In the modern study circle, the topic of digitization in education and its impact on learning is one of the most important issues. The purpose of the study is to analyze the impact of the use of digital platforms on the study and development of English language skills in teenagers. This study also aims to fill a gap in the field of language education and psycholinguistics, particularly the aspect of word recall, using the application of a mobile digital platform for practice. Existing studies have generally emphasized the importance and effectiveness of traditional language learning methods, but the number of studies analyzing the use of digital platforms is still limited. The study used a pre-post survey method, which aimed to determine the baseline performance of all participants and the rate of change after practice using quizlet for Group 1 compared to the traditional methods used by Group 2 for English learning and memorization of new words. The sample consisted of 100 students from Russia studying English. Students were divided into two groups, where Group 1 used the Quizlet app and Group 2 used traditional word study methods. After two weeks of studying vocabulary, the participants demonstrated positive dynamics of word memorization. Findings showed that in Group 1, which used the program, 30% of participants successfully achieved a high level of vocabulary, while an additional 57% saw their vocabulary skills improve to an average level. Only 12% demonstrated a low level of vocabulary. In contrast, Group 2 showed minimal changes in their vocabulary. Only 14% of participants retained a high level of vocabulary, 70% were medium, and 15% were low. The obtained results can help develop new educational programs and mobile applications for language learning based on interactive methods and approaches. The obtained results can be useful for language education in terms of the possibility of integrating methods using the Quizlet program to improve the development of students’ vocabulary and lexical expressions of the English language. This study makes a significant contribution to the field of foreign language learning, providing results that emphasize the effectiveness of using digital mobile resources for learning English and have a positive effect on the psycholinguistic aspect of memorizing new words. By demonstrating significant improvements in vocabulary among participants, this study highlights the potential of mobile applications to support traditional teaching methods and offers a viable alternative for language teaching, especially in the digital age.